PENGARUH JENIS ISOLAT LIGNIN DAN NISBAH MOL L/F PADA PEREKAT LIGNIN FORMALDEHIDA TERHADAP KETEGUHAN REKAT KAYU LAPIS TUSAM * - Adi Santoso; Surdiding Ruhendi; Suminar S Achmadi; Endang Suhendang (Jurnal Penelitian Hasil Hutan, 1995)
It has been known that lignin can be used as plywood adhesive for exterior purpose. The sources of lignin are black liquor indulin-AT (commercial lignin).A study on lignin formaldehyde  resin making from  black liquor and indulin-AT was done and the results were  used to predict  the effect of lignin  isolate type and L/F  mole ratio on plywood bonding strength. The results show taht the type of lignin isolate and L/F  mole ratio have highly significant  effect on plywood bonding strength. The mole ratio L/F of 1 : 1.50 and 1:1.75 by lignin isolate from  indulin-AT result in plywood bonding strength about 7.5 kg/cm2 and 8.8 kg/cm2,   respectively. The bonding strength of these plywood conforms with the 1983 Japanese standard for exterior purpose.